Fundamentals of Islamic money and capital markets - Omar, Azmi (John Wiley, 2013)
The first comprehensive guide to Islamic financial markets Based on the course taught at the International Islamic University Malaysia, this is the first book on Islamic finance to focus exclusively on money and capital markets. Covering basic concepts as well as current practices in Islamic financial markets, the book features case studies from real markets. It outlines the theory of money in terms of value, supply, and demand, while explaining the Islamic capital markets in terms of classifications, types of operations, valuations of securities, Islamic unit trust, ETFs, Islamic sto.